Zhawahir al-Azdawajiyyah al-Lughawiyyah fi Ittishalat JamaÃ¡h al-Ãrb fi Indunisiyya (Dirasah al-Halah bi Malang Jawa al-Syarqiyyah) - Nashoih, Afif Kholisun; Fitriyah, Tika (Institut Agama Islam Negeri Curup, 2021)
This research aims to describe and classify the language used by Arab Embong Community in their daily life. Â Language and society always influence each other. The development of language is also along with the development of society. Therefore the study of sociolinguistics as a scientific discipline in which studying language in relation to society is always interesting. The problem in this study is the language used by Embong Arab Community which is an immigrant Arab Community in Malang. This was a field research with a qualitative descriptive method which was investigated using the Diglossia theory. The methods of data collection were observation and interview. The results of this research indicated that the Embong Arab community used three languages, namely Fusha and Amiyah Arabic, Indonesian and Javanese. The three languages were used interchangeably according to the purpose of communication. Fusha Arabic, as the official and unifying language among Arabs, was rarely spoken. They preferred to choose Amiyah Arabic to communicate as a non-standard language variety. However, their Amiyah language was different from the Yemeni Arabs in general. This was due to their long-standing interactions with the local population. The unique thing was that even though they were of Arab descent, due to their high level of interactions with the local population, they often used non-formal Indonesian and Javanese Ngoko in their daily lives. So there were two varieties of diglossia in Embong Arab Community, namely high level language consisting of Fusha Arabic and formal Indonesian and low level language consisting of Amiyah Arabic, non-formal Indonesian and Javanese Ngoko).